Evaluation of Drug Use Patterns in Intensive Care Unit of Tertiary Care Hospital: A Descriptive Cross-Sectional Study - Ghimire, Rinku; Shreewastav, Rupesh Kumar (Journal of Nobel Medical College, 2021)
Background: Prescription of rational drugs is needed to save critically ill patients. This study was conducted to assess the prescription patterns of drugs in the intensive care unit.Materials and Methods: A descriptive cross-sectional study among patients admitted in intensive care unit from March 2020 to February 2021 after approval from the Institutional Review Committee (ref no. 344 /2019). Demographic profile, prescription patterns, the average number of drugs used, route of administration, and duration of hospitalization were recorded based on the pre-structured questionnaires. Convenient sampling was chosen. Data were analyzed by SPSS, version 20.Results: Prescription patterns of 225 were analyzed. The mean age was 55.60 ± 20.16 years with a male predominance of 131(58.2%). Cardiac disorders 57(25.3%) were the most common admitting diagnosis followed by pulmonary, neurological, and kidney disorders. The average length of hospital stay was 4.14 days (range 1-38 days). A total of 887 drugs were prescribed. The mean number of drugs prescribed per patient was 7.71 ± 1.92. Parenteral drugs accounted for 81.39%. Antibiotics were prescribed to all patients. Intravenous fluids were given to 62.2% of patients, blood and blood products to 21.33%. Thromboprophylaxis was used in 15 (6.7%) patients. Seven hundred twenty-two (81.39%) drugs were injectables, 129(14.54%) were used by the oral or nasogastric route and 36 (4.05%) were inhaled drugs.Conclusion: Newer generations antibiotics were the most commonly prescribed drugs. Pantoprazole, Metoclopramide, and Hydrocortisone were the top three most commonly prescribed individual drugs. There was marked underuse of thromboprophylaxis, analgesics, and sedatives.